Ellagic Acid Enhances the Efficacy of PI3K Inhibitor GDC-0941 in Breast Cancer Cells - Shi, L.; Gao, X.; Li, X.; Jiang, N.; Luo, F.; Gu, C.; Chen, M.; Cheng, H.; Liu, P. (Current Molecular Medicine, 2015)
The fact that the phosphatidylinositol 3 kinase (PI3K) signaling pathway is one of the most frequently deregulated signaling networks has triggered intensive efforts in the development of PI3K pathway inhibitors. However, recent clinical trial data have shown only limited activity of PI3K inhibitors at tolerated doses. Thus, there is an urgent need to identify rational combination therapy to improve the efficacy of PI3K-targeted cancer treatment. In this study, we investigated if dietary compound ellagic acid (EA) could improve the therapeutic efficacy of PI3K inhibitor GDC-0941 in breast cancer. Specifically, using a panel of breast cancer cell lines, we showed that combined use of EA and GDC-0941 significantly inhibited cell growth under attached and detached conditions, blocked migration and invasion in vitro as well as tumor initiation and metastasis in vivo. Furthermore, we found that EA promoted apoptosis and further reduced AKT/mTOR activation in GDC-0941- treated breast cancer cells. Together, our data suggest that EA may be a safe and effective agent to boost the efficacy of PI3K-directed breast cancer therapy and that such drug combination may merit further clinical investigation.
Keywords: targeted therapy